Exploring the Impact of Cigarette Smoke Extracts on Vitamin B12: Insights into the Transformation of Methylcobalamin and Hydroxycobalamin to Cyanocobalamin through In Vitro Evaluation - Mazhar Salim Al Zoubi; Mus’aab A. Al-Oun; Fatima Yacoub Abusahyoun; Manal Issam Abualarja; Asmaa Al Smadi; Bahaa Al-Trad; Sura A. Awadin; Khalid Al-Batayneh; Mai Elaarag; Raed M. Al-Zoubi (Biochemistry Research International)
Vitamin B12 (cobalamin) is a water-soluble molecule required for the proper functioning of metabolism, blood and DNA synthesis, and neurological development. Vitamin B12 exists in several forms: methylcobalamin (MeCbl), adenosylcobalamin (AdoCbl), hydroxycobalamin (OHCbl), and cyanocobalamin (CNCbl). This study aimed to evaluate the effect of cigarette smoke on the chemical structure of methylcobalamin and hydroxycobalamin forms of vitamin B12. MeCbl and OHCbl were markedly affected by exposure to cigarette smoke. The resemblance of the Rt between MeCbl and OHCbl and CNCbl indicates that exposure to cigarette smoke extracts chemically alters MeCbl and OHCbl to CNCbl, warranting in vivo research investigations.